Pay disparities within top management teams, marketization and firms' innovation: evidence from China. Issue 4 (17th October 2022) - Sun, Bo; Ruan, Ao; Peng, Biyu; Liu, Shanshi
Abstract: Using executive resume data of China's listed companies between 2006 and 2016, we investigated the relationship between pay disparities within top management teams (TMT) and firms' innovation performance. Specifically, we assessed two dimensions of pay disparities: vertical pay disparity between CEOs and non-CEO managers, and horizontal pay disparity among non-CEO managers. Considering the difference in regional marketization progress, we also explored the moderating effect of marketization degree on this relation. It is found that: with vertical pay disparity increasing by 1%, firms' innovation performance is improved by 2.3%; with horizontal pay disparity increasing, firms' innovation performance is promoted first and then restrained; higher marketization degree strengthens the incentive effects of both vertical and horizontal pay disparity. But the grouped regression results show that, in state-owned enterprises, horizontal pay disparity is only negatively associated with innovation. The theoretical and practical significance of the research is discussed at the end of the paper.